Kepraktisan Media Pembelajaran Matematika Video Animasi Berbantuan Adobe After Effect Berbasis Problem Based Learning - Oktavianah, Rini; Nurfalah, Edy (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
Mathematics is one of the important sciences learned by students. However, in learning, most consider it a very difficult subject, because in learning mathematics there are many formulas and calculations that occur to solve problems and mathematics is one of the subjects shared by students because in mathematics lessons only find numbers, formulas, and graphs. This makes students less interested and boring. It is undeniable that the learning media used in learning will affect students' interest in learning and understanding concepts. the use of learning resources is still limited to the use of materials in the form of textbooks. This study aims to determine the level of validity, practicality and effectiveness of animated video learning media. This study aims to determine the validity of the development of animation video mathematics learning media assisted by Adobe After Effects based on Problem Based Learning for junior high school students. This research is an R&D (Research and Development) research. The development model used in this study is a 4-D model which is divided into 4 stages, namely, the Define, Design, Development and Disseminate stages. Media testing was conducted in class VII D involving 25 students. The results of the practicality test based on the learning implementation sheet obtained a score of 3.72 while based on the response questionnaire, a percentage of 64% of good responses was obtained. So that the videos developed are practically used for learning.